Comparative analysis of tools dedicated to building Single Page Applications – AngularJs, ReactJS, Ember.js - Nowacki, Radosław; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2016)
The subject of this article is a comparative analysis of some of the most popular frameworks, of JavaScript programming language, dedicated to creating Single Page Applications. There were four criteria accepted for the purpose of the research. The criteria are: difficulty of learning the given library, additional tools specific for given framework, performance on desktop devices and performance on mobile devices.